Glossopharyngeal and Hypoglossal Nerve Paralysis Secondary to Prevertebral Phlegmon - Ryunosuke Fukushi; Izaya Ogon; Yoshinori Terashima; Hiroyuki Takashima; Tsutomu Oshigiri; Noriyuki Iesato; Mitsunori Yoshimoto; Makoto Emori; Atsushi Teramoto; Toshihiko Yamashita (Case Reports in Orthopedics)
A 50-year-old man presented to the clinic with severe neck pain, fever, and difficulty breathing and was subsequently admitted to the local orthopedics department with possible retropharyngeal abscess and pyogenic spondylitis. Antibiotic therapy was initiated; however, due to poor oxygenation, he was referred and transferred to our department and admitted. Magnetic resonance imaging showed signal changes at the left C1/2 lateral atlantoaxial joint, posterior pharynx, longus colli muscle, carotid space, and medial deep cervical region, predominantly on the left side. In addition, despite lymph node enlargement from the posterior pharynx to the deep cervical region, there was no abscess formation. There were no signs of a space-occupying lesion or signal changes in the jugular foramen. One day postadmission, the patient’s temperature had risen to 39.1°C and his SpO2 had fallen. His neck pain had also worsened, and emergency surgery was decided. Preoperatively, we suspected retropharyngeal abscess and pyogenic spondylitis. On day 13 postadmission, the patient exhibited dysphagia, deviated tongue protrusion, and the curtain sign. Glossopharyngeal and hypoglossal nerve paralysis were diagnosed. The patient’s swallowing functions recovered and he was discharged on day 36. We experienced a case of glossopharyngeal and hypoglossal nerve paralysis secondary to pyogenic cervical facet joint arthritis.